THE METHODOLOGY OF PREPARING PRIMARY SCHOOL STUDENTS FOR INTERNATIONAL ASSESSMENT SYSTEMS OF READING LITERACY - Ahmadaliyeva , Gulhayo; Rajabova, Nodirabegim (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
This thesis discusses the methodology for preparing primary school students for international assessment systems of reading literacy, in particular the PIRLS program. The study developed effective teaching methods based on methods, innovative technologies and diagnostic approaches aimed at developing students' reading, comprehension and analysis skills. The results show that the use of active learning methods and interactive tools has a positive effect on improving students' reading literacy.